Comparison of pulp sludge compost effectivity of three different decomposers to the growth of geronggang (Cratoxylon arborescens) seedlings - Siti Wahyuningsih; Agus Winarsih; Lolia Santi (Jurnal Penelitian Kehutanan Wallacea, 2021)
Pulp residue from liquid waste processing is suitable for compost materials, except for its high CN ratioso it needs composting to reduce the CN ratio. Geronggang is a nativepeat swamp species suitable for peat rehabilitation. The study aims to test pulp sludge compost quality enriched with three different decomposersto the growth of geronggang (Cratoxylum arborescens)seedlings. The sludge composting was incubated for a monthusing threespecies of decomposers, i.e., Phanerochaete chrysosporium(C); Penicillium citrinumand Penicillium oxalicum (CO); P. chrysosporium, P. citrinumand P. oxalicum (CCO). The compost is weighed and placed around the seedling's roots area with varies dosages equal to2, 4, 6, 8, 10, 12, 14,and 16 ton ha-1. The height and diameter of the seedlings were recorded for six months. Data was examined using ANOVA followed with DMRT at a 5% significance. The sludge compost in this study has CN ratio, Total N (%), P2O5(%) and K2O (%) about 40.22-44.5; 1.04-1.11; 1.05-1.13; 1.05-1.13, respectively. Statistically, the height increment of seedlings after the sludge compost application enriched with the CO was different from the CCO. However, the seedling's height rise was not statistically different at the dosages variation treatment. The raise of seedlings diameter after CO treatment at a dosage equal to 6 and 12 tonha-1was significantly different to the CCO at a dosage equal to 12 ton ha-1. However, the rise of seedling's diameter was not significantly different at decomposers' variation treatment.The future study can be aimed to gain compost that meets the national standard.